2020
DOI: 10.1242/jcs.237503
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of malignancy in glioblastoma cells are linked to mitochondrial Ca2+ uniporter upregulation and higher intracellular Ca2+ levels

Abstract: Glioblastoma (GBM) is one of the most malignant brain tumours and, despite advances in treatment modalities, it remains largely incurable. Ca 2+ regulation and dynamics play crucial roles in different aspects of cancer, but they have never been investigated in detail in GBM. Here, we report that spontaneous Ca 2+ waves in GBM cells cause unusual intracellular Ca 2+ ([Ca 2+ ] i) elevations (>1 μM), often propagating through tumour microtubes (TMs) connecting adjacent cells. This unusual [Ca 2+ ] i elevation is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…Our findings highlighted the carcinogenicity of MCU in gastric cancer, which can regulate tumor growth and invasiveness, and could become a promising therapeutic target for gastric cancer. Previous studies have found that MCU is highly expressed in TNBC, 8 colon cancer, 10 glioma, 9 hepatocellular carcinoma 11 and pancreatic ductal adenocarcinoma. 12 In this study, high MCU expression was found in gastric cancer tissues.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Our findings highlighted the carcinogenicity of MCU in gastric cancer, which can regulate tumor growth and invasiveness, and could become a promising therapeutic target for gastric cancer. Previous studies have found that MCU is highly expressed in TNBC, 8 colon cancer, 10 glioma, 9 hepatocellular carcinoma 11 and pancreatic ductal adenocarcinoma. 12 In this study, high MCU expression was found in gastric cancer tissues.…”
Section: Discussionmentioning
confidence: 98%
“…MCU silencing reduces the proliferation of glioma cells. 9 Abnormally expressed MCU is associated with poor prognosis of colon cancer patients. 10 MCU knockdown can promote the migration and metastasis of colon cancer cells and reduce the mitochondrial membrane potential.…”
Section: Introductionmentioning
confidence: 99%
“…31 In comparison, accumulating evidence indicates that mitochondrial Ca 2+ uptake mediated by upregulated MCU significantly promotes cell proliferation in cancers. Li et al 32 . showed that MCU overexpression is associated with the glioblastoma cell proliferation but not the induction of cell death.…”
Section: Discussionmentioning
confidence: 99%
“…In this phase, BK channels are overexpressed in their spliced isoforms, which increases their sensitivity to the calcium concentration. Therefore, despite the fact that the RMP is still below the BK threshold, transient cytosolic calcium rise (Catacuzzeno et al, 2011;Li et al, 2020) could depolarize the cell and shift the activation curve to a more hyperpolarized potential allowing a transient opening of BK channels ( Figure 1C). Under these conditions, BK channels can contribute efficiently and summate with Kir4.1 channels in controlling total efflux of potassium and consequent shrinkage.…”
Section: Kir41 and Bk Channels: A Summative Link?mentioning
confidence: 99%